The mystery of the hard luck rodeo - Saunders, Susan; Rosales, Melodye (New York : Random House, 1989)
Fourth grader Tommy Price, Jr., and his friend Bonnie Sue, whose families work for area rodeos, investigate the mysterious occurrences that threaten to close down the Red Bluffs Rodeo and stop country singer Mel Jones from performing.
Keywords: Rodeos -- Fiction; Mystery and detective stories